Author-Related Concepts in Academic Writing Revisited: A Scoping Review - Елена Тихонова; Lilia Raitskaya (Journal of Language and Education)
Introduction: Various linguistic mechanisms and devices are applied in academic writing to communicate the opinion and valuations of the authors and engage with their readers. The concepts of author’s voice, stance and identity stand out among numerous notions describing various aspects related to the author in the written academic discourse. The scoping review aims to synthesize the knowledge on those concepts in the international publications with a view to defining frequently and interchangeably used terms.